Penyebab Kehampaan Gabah pada Persilangan Padi antar Subspesies - Hermanasari, Rini; Aswidinnoor, Hajrial; Trikoesoemaningtyas, ,; Suwarno, , (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
ABSTRACTThe  objective  of  the  research  was  to  study  the  factors  effecting  unfilled  grains  in  intersubspecific  hybridization.  The  research  was  conducted  at  Muara, Bogor  from  April  2005  to  February  2006.  The  materials  used  in the research were  ten  F1 hybrid  combinations.  The evaluation was done by crossing the hybrids to Ciherang and it was resiprocal. A randomized block design with three replications were arranged in greenhouse. The results showed that five cross combinations produced higher unfilled grains and lower pollen fertility due to defective male gamets. The cross combinations that is Akitakomaci/IR64, Akitakomaci/Wayrarem, Akitakomaci/Salumpikit, Akitakomaci/Ketupat, and Akitakomaci/Kewal. Another five cross combinations produced normal pollen fertility but high unfilled grains. The high unfilled grains of four cross combinations was due to defective female gamets. The cross combination that is IR64/Sirendah Pulen, IR64/Lampung Putih, IR64/Lampung Kuning, and IR64/Mesir.  The other cross combination was due to defective male and female gamets  namely IR64/Brentel. Key words:  Unfilled grain, F1 hybrids, male gamets, female gamets